Numerical Study of a Wide-Angle and Polarization-Insensitive Ultrabroadband Metamaterial Absorber in Visible and Near-Infrared Region - Nguyen Thi Quynh Hoa; Phan Huu Lam; Phan Duy Tung; Tran Sy Tuan; Hugo Nguyen (IEEE Photonics Journal)
An ultrabroadband metamaterial absorber structure based on a periodic array of metallic-dielectric multilayered conical frustums is numerically investigated and proposed. The metamaterial absorber indicated an absorptivity of higher than 90%, which covered the visible and near-infrared region at 480–1480 nm, and a relative absorption bandwidth of 102%. The high absorptivity can be maintained with large incident angles up to 60° under both transverse electric and transverse magnetic polarizations. Furthermore, the proposed absorber exhibits polarization insensitivity owing to its rotational symmetry structure. Compared with the previously reported ultrabroadband metamaterial absorbers, the design in this work indicates high practical feasibility in terms of a compact structure for a large bandwidth, a wide incident angle, and polarization insensitivity, thereby suggesting its promising application, for example, in solar cells and thermal emitters.